Mitična oseba Šent v slovenskem izročilu - Mencej, Mirjam (Studia mythologica Slavica, 1999)
The authoress endeavours to discover whether Šent, the myhical person written about by Davorin Terstenjak, is but a product of Trstenjak's imagination, or maby a record of genuine belif
Keywords: ljudsko izročilo; ethnology; etnologija; mitologija; mythology; verovanja; oral literature; ljudsko slovstvo